Involvement of secondary metabolites in the pathogenesis of the American foulbrood of honey bees caused by Paenibacillus larvae. Issue 6 (27th June 2015) - Müller, Sebastian; Garcia-Gonzalez, Eva; Genersch, Elke; Süssmuth, Roderich D.
<x xml:space="preserve">Abstract</x> The Gram-positive spore-forming bacterium Paenibacillus larvae is the causative agent of the fatal disease American Foulbrood of the western honey bee. This article highlights recent findings on secondary metabolites synthesized by P. larvae.